Complete mitochondrial genome of the Onychostruthus taczanowskii (Aves, Passeridae) and its phylogenetic analysis. (3rd July 2016) - Ma, Yonggui; Wang, Xiaoyang; Huang, Yuan; Lei, Fumin
Abstract: The complete mitochondrial genome sequence of Onychostruthus taczanowskii consisted 16 917 bp, the genome harbored the same gene order with that of other birds, contained 13 protein-coding genes, 22 tRNAs, 2 rRNAs and 1 non-coding control region. The all tRNAs formed typical cloverleaf secondary structures, except tRNA Ser (AGN) and tRNA Phe . The control region was located between tRNA Glu and tRNA Phe with 1310 bp in length, which consist of three domains: highly variable domain I, central conserved domain II and conserved sequence domain III. According to the phylogenetic analysis, Onychostruthus taczanowskii had a closer relationship with Pyrgilauda ruficollis, and Passer montanus were sister to them.